Adaptive circular enclosure colour distribution geometrical model utilizing point-in-polygon for segregation between lips and skin pixels - Lee, Hao Wei; Seng, Kah Phooi *; Chia, Wai Chong *; Ang, Li-Minn (2012)
This paper is inspired from various boundary determination techniques which are used for segregating colours between background, skin and lips. Basic concept for this technique is based on colour segmentation with CIELAB colourspace utilized for justifiable reasons. Using LAB colour-space, lips colours were compiled into a colour-map and processed accordingly to our proposed algorithm of adaptive circular enclosure. Algorithm output was determined as a series of coordinates symbolizing boundary values surrounding colourmap. Separation of colours is based on these boundaries by creating a freeform polygon that defines if colour-value either belongs within colour-boundary polygon or not. This technique is famously known as the point in-polygon technique. Proposed technique evaluation uses XM2VTS database based on false positive and false-negative to compute segmentation error. Simulation shows proposed algorithm yields segmented error of 5.55% with accuracy of 94.45%.